2016
DOI: 10.1088/1612-202x/aa532e
|View full text |Cite
|
Sign up to set email alerts
|

Statics and dynamics of a self-bound dipolar matter-wave droplet

Abstract: Abstract.We study the statics and dynamics of a stable, mobile, self-bound three-dimensional dipolar matter-wave droplet created in the presence of a tiny repulsive three-body interaction. In frontal collision with an impact parameter and in angular collision at large velocities along all directions two droplets behave like quantum solitons. Such collision is found to be quasi elastic and the droplets emerge undeformed after collision without any change of velocity. However, in a collision at small velocities … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 63 publications
0
20
0
Order By: Relevance
“…It is expected that the dynamics of quantum balls will be independent of the details of the mechanism responsible for self binding and we do not believe that the results obtained here are so peculiar as to have no general validity. In fact, a preliminary study revealed similar dynamics for quantum balls made of dipolar atoms [18]. A stationary quantum ball can be formed for the two-body attraction above a critical value in the 3D GP equation for any finite three-body repulsion.…”
Section: Introductionmentioning
confidence: 81%
“…It is expected that the dynamics of quantum balls will be independent of the details of the mechanism responsible for self binding and we do not believe that the results obtained here are so peculiar as to have no general validity. In fact, a preliminary study revealed similar dynamics for quantum balls made of dipolar atoms [18]. A stationary quantum ball can be formed for the two-body attraction above a critical value in the 3D GP equation for any finite three-body repulsion.…”
Section: Introductionmentioning
confidence: 81%
“…In the case of the repulsive SPM, the LHY theory, which introduces effects of quantum fluctuations around the mean-field state, gives rise to post-mean-field corrections which are crucially important for the stabilization of self-trapped QDs by means of the effective higher-order self-repulsion [32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48]. In particular, it removes the collapse induced by the attractive XPM at = N N thr , see equation (8).…”
Section: Mms Under the Action Of The Lhy Termsmentioning
confidence: 99%
“…[38] and [39], respectively. The dynamics of QDs in dipolar BECs was analyzed in detail in recent works [40]- [49].…”
Section: Introductionmentioning
confidence: 99%